Analisis Sistem Informasi Akuntansi Penggajian Dan Pengupahan Sebagai Alat Pengendalian Intern (Studi Kasus Pada Pt Merapi Agung Lestari Malang) - Galuh Budi Astuti; Agustinus Kristian Wicaksono (Akubis : Jurnal Akuntansi dan Bisnis, 2021)
The purpose of this study was to analyze payroll and wage accounting information systems as a means of internal control at PT. Merapi Agung Lestari. Type of case study research. Data collection techniques through observation, interviews, and documentation. The data analysis technique used is descriptive qualitative analysis. The problem is that the payroll and wage accounting information system is still weak. This is evidenced by the absence of employee salary slips, one copy of the proof of payment document, only two copies of the ticket transfer document, only one copy of the proof of payment document. The cause of the problem is because the company does not understand the importance of these documents. As a result, fraud can occur and company activities cannot run properly. The results of the analysis indicate the need for additional documents in the form of payslips used to record details of employee salaries, the need for additional duplication of several documents such as proof of payment documents and transfer tickets and improving payroll and wage systems and procedures so that internal control can run effectively.